2019
DOI: 10.12998/wjcc.v7.i21.3662
|View full text |Cite
|
Sign up to set email alerts
|

Hypoparathyroidism with Fahr’s syndrome: A case report and review of the literature

Abstract: BACKGROUNDHypoparathyroidism with basal ganglia calcification is clinically rare. Here, we report a case of Fahr’s syndrome due to hypoparathyroidism and review the literature in terms of etiology, clinical manifestation, diagnosis, and treatment.CASE SUMMARYA 62-year-old man experienced repeated twitching of both hands in recent 10 years. On July 28, 2017, the patient was admitted to our hospital due to slow response and speech difficulties. On medical examinations, he had a positive Chvostek sign, while no A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 35 publications
0
14
0
7
Order By: Relevance
“…9,10 Hypoparathyroidism is a common cause of basal ganglia calcification, and its etiology can be idiopathic (uncommon condition characterized by the absence or atrophy of the parathyroid glands) or secondary (usually a complication of thyroid surgery). 5,11,12 As regards the present case, the patient had no history of neck surgery, neither there was evidence of an infectious disease. It were not found any vitamin deficiencies or signs of malnutrition.…”
Section: Discussion/conclusionmentioning
confidence: 54%
See 1 more Smart Citation
“…9,10 Hypoparathyroidism is a common cause of basal ganglia calcification, and its etiology can be idiopathic (uncommon condition characterized by the absence or atrophy of the parathyroid glands) or secondary (usually a complication of thyroid surgery). 5,11,12 As regards the present case, the patient had no history of neck surgery, neither there was evidence of an infectious disease. It were not found any vitamin deficiencies or signs of malnutrition.…”
Section: Discussion/conclusionmentioning
confidence: 54%
“…Multiple clinical conditions are associated with intracranial calcifications, including infectious diseases (acquired immune deficiency syndrome, toxoplasmosis, cytomegalovirus, herpes simplex, brucellosis), genetic conditions (Fahr's disease, pseudohypothyroidism), vascular, toxic exposure (lead poisoning, hypervitaminosis D), autoimmune disease (systemic lupus), and endocrine disorders (calcium/phosphorus abnormalities) 9,10 . Hypoparathyroidism is a common cause of basal ganglia calcification, and its etiology can be idiopathic (uncommon condition characterized by the absence or atrophy of the parathyroid glands) or secondary (usually a complication of thyroid surgery) 5,11,12 …”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Idiopathic hypoparathyroidism induced FS is diagnosed based on findings of hypocalcemia, hyperphosphatemia, and hypoparathyroid hormone with additional findings of calcium deposition in the basal ganglia seen most commonly on CT imaging. As previously mentioned, these effects on the basal ganglia result in abnormal neuropsychiatric motor activity [11].…”
Section: Discussionmentioning
confidence: 93%
“…Mahmood et al reported a case of movement disorder in a patient with Fahr's syndrome due to hypoparathyroidism [ 6 ]. Zhou et al also highlighted a case of Fahr's syndrome due to primary hypoparathyroidism presenting with movement disorders [ 7 ]. Similarly, our patient had Fahr's syndrome secondary to hypoparathyroidism manifesting as aphasia and parkinsonian features, rarely reported in the literature.…”
Section: Discussionmentioning
confidence: 99%